"Bisexuality Isn't Exclusionary": A Qualitative Examination of Bisexual Definitions and Gender Inclusivity Concerns among Plurisexual Women. Issue 4 (14th November 2022) - Cipriano, Allison E.; Nguyen, Daniel; Holland, Kathryn J.
Abstract: The current study investigated how plurisexual women of varying identities conceptualize bisexuality. We conducted 25 semi-structured interviews women with attraction to more than one gender. Using thematic analysis, we identified three overarching themes: (1) definitions of bisexuality differ by one's identity label, (2) concerns about sexual identity label inclusivity, and (3) outcomes of inclusivity concerns among women attracted to more than one gender. Non-bisexual women (i.e., pansexual, queer) defined bisexuality as limited to attraction to cisgender men and women and critiqued bisexuality as reinforcing the traditional gender binary. However, bisexual women defined bisexuality as attraction to two or more genders, described bisexuality as inclusive of attractions to all genders, and negative psychological outcomes as a result of the debate around bisexual gender inclusivity. Our findings suggest that sexual identity researchers might consider adopting the definition of bisexuality provided by bisexual women in this sample: attraction to more than one gender.